APLIKASI BANK SAMPAH BERKAH MELIMPAH BERBASIS WEBSITE PADA KELURAHAN NANGGEWER - Fauzia Hayati Rahmah (2022)
In the management of services at the Abundant Blessing Waste Bank in Nanggewer Village, it is still carried out manually, the management is carried out by officers using paper media. This can allow data loss due to human error. This study aims to help solve problems regarding the management of services that have not been computerized. The flow of this study uses the SDLC (System Development Life Cycle) method with a Waterfall approach. This waterfall approach has a clear and structured system research workflow. At the design stage, the author uses object-oriented tools, namely UML (Unified Modelling Language) by using case diagram modeling, activity diagrams, sequence diagrams, and class diagrams. Application system development uses the PHP programming language as well as the CodeIgniter framework. In testing the application system, the author performed a test using the Black Box method. This research produced a website-based application system that is expected to assist officers in managing the services of the Berkah Melimpah Waste Bank, the possibility of loss of data from recording customer waste deposits and weighing reports can also be resolved because the data has been stored properly into the database system.